"Be Ready for It": School Counselors' Experiences With Subpoena and Testifying in Court. (2017) - DeCino, Daniel A.; Waalkes, Philip L.; Matos, Cristina
School counselors' experiences with subpoenas and testifying in court remain relatively unknown. In this narrative study, we examined 14 school counselors' experiences with the legal system. The data analysis process uncovered three themes in participants' experiences: (a) professional intentions, (b) interpersonal connections, and (c) experiences with legal proceedings. We discuss implications for school counselors and counselor educators regarding legal proceedings and directions for future research.